Half - om - half : Kunst - vee - geschiedenis : brochure. - Smolders, Frans; de Weijer, Joost van; Historisch Museum, Apeldoorn (Apeldoorn : Van Reekum Museum Apeldoorn, 2001)
Toebosch, Moniek ; Felius, Marleen ; Cremer, Jan ; Xu Bing ; Geelen, Guido ; van Mourik, G. ; Balk, Christa ; Koivista, Kaisu ; Strobl, Ingeborg ; Smit, Carolein ; de Vries, Jaap ; Gouffé, J. ; Kreunen, A. ; Mulders, Marc ; Atelier van Lieshout ; Kissina, Julia ; Smulders, Margriet
Nederlands
Half - om - half : Kunst - vee - geschiedenis, Historisch Museum, Apeldoorn, Van Reekum Museum, Apeldoorn, 13 april t/m 2 september 2001
boek